Adapting to rapidly transforming seascapes in the Mid- to Late Holocene, southeastern Australia - Rogers, Ashleigh J.; Kennedy, David M.; David, Bruno; Mullett, Russell; Fresløv, Joanna; Petchey, Fiona; Arnold, Lee J.; Demuro, Martina; , GunaiKurnai Land and Waters Aboriginal Corporation; Drayton, Cheryl; Mullett, Howard (Frontiers in Environmental Archaeology, 2025)
Aquatic environments are highly dynamic. They are characterized by rapid and often unpredictable transformations driven by sea-level fluctuations, climate change, tectonic activity, and anthropic land-and-sea use practices that result in large-scale environmental shifts. Globally, archaeology has documented how people adapt and respond to these changes by altering subsistence strategies, settlement patterns, travel routes, and technologies to meet the challenges of a constantly transforming aquascape. Coastal regions, in particular, have both challenged and sustained human populations, offering abundant resources while also requiring significant adaptability in response to regular and, at times, substantial sea level fluctuations from the terminal Pleistocene throughout the Holocene. Using an interdisciplinary approach that pairs coastal geomorphology and archaeology, we investigated the Mid- to Late Holocene development of a barrier island in southeast Victoria, Australia–the development of which prompted wider inshore ecosystem transformations. Results from archaeological excavations demonstrate that people responded to coastal transformations by flexibly adjusting their lifeways and subsistence strategies over short time-scales and, through firing of the landscape, shaped surrounding ecosystems in return. Understanding how populations navigated these past changes, both through immediate adaptive responses and long-term cultural transformations, provides valuable insights into the resilience and adaptability of human societies in the face of environmental uncertainty.